Expectations for cross-ethnic inclusion by Asian American children and adolescents. (August 2020) - Hitti, Aline; Elenbaas, Laura; Noh, Jee Young; Rizzo, Michael T.; Cooley, Shelby; Killen, Melanie
Asian American youth's inclusion decisions were investigated in cross-ethnic peer contexts (Asian and non-Asian). Ten-, 13-, and 16-year-old participants ( N = 134), enrolled in U.S. schools, decided whether to include a same-ethnic peer with different interests or a different-ethnic peer with similar interests. Findings showed that with age, participants more frequently included a peer who shared interests even when this peer was not of the same ethnicity. Participants expected their peer groups to be equally inclusive of others of both ethnic backgrounds, and expected that in-group parents would be less inclusive of cross-ethnic peers. In addition, adolescents expected parents to have prejudicial attitudes about ethnic out-group members. Views about peer group and in-group parents' inclusivity diverged from adolescents' own inclusivity. These findings point to areas for intervention regarding the promotion of cross-group friendships and the reduction of prejudice.